ISO 14001 implementation: the level of awareness and education of AEM employees towards protecting environment. - Hashim, Ismail (2001)
In the world today environment protection is one of the main issue that played in the people mind. Everyday environment issue such as open burning, recycling, forest destruction and so on viewed in the TV news and newspaper. Now, the issue had come to Malaysia where the government try to educate people to protect the environment. As a prove the launch of recycle campaign, “Think before throw”. Recycling reduces the need for landfills or dumpsites. Should rubbish double along with the population in Malaysia, we may very soon be sharing our homes with dumpsites. Imagine not having to take the rubbish out anymore. Therefore the writer take this opportunity to do a research in this aspect where the implementation of ISO 14001 that also known as Environmental Management System (EMS) at Aiwa Electronic Malaysia (AEM) Sdn. Bhd as the a model. It cannot be a doubt that ISO 14001 implementation has a link with the protection of environment, thus the action of AEM employees that educated by EMS at the workplace is measured. The writer hope that the implementation of ISO 14001 activities that relate to environment protection can be brought outside the workplace. Therefore it can increase the level of awareness in protecting environment not only to AEM family but the whole community. To make this succeed, the level of training and education towards protecting environment is a vital step. Therefore this study also focus to this aspect to make sure this dream come true. Finally let us make this dream come true by joining hands together before this world reach its time and cannot handle the pollution anymore.